Capital expenditure and levelized cost of electricity of photovoltaic plants and wind turbines – Development by 2050. (February 2022) - Sens, Lucas; Neuling, Ulf; Kaltschmitt, Martin
Abstract: Over the last decade, the levelized cost of electricity (LCOE) of solar and wind energy dropped extraordinary. Within this context, this paper aims to project the capital expenditures (CAPEX) of photovoltaic plants, onshore and offshore wind turbines for 2030 and 2050 by using the experience curve theory. Based on these, LCOE for 2020, 2030 and 2050 are estimated, investigated regarding their sensitivities and compared to fossil fuel based power plants. CAPEX projections amount to 250 to 430 €2020 /kWel (2030) and 170 to 330 €2020 /kWel (2050) for photovoltaic plants, 940 to 1, 210 €2020 /kWel (2030) and 820 to 970 €2020 /kWel (2050) for onshore wind turbines and 1, 730 to 2, 570 €2020 /kWel (2030) and 1, 420 to 2, 360 €2020 /kWel (2050) for offshore wind turbines. Based on these results the LCOE of photovoltaic plants are estimated to drop up to more than 70 % (2050), while for wind turbines reductions up to 50 % (2050) are calculated. The highest sensitivity of the LCOE was identified for a variation of the CAPEX and annual full load hours. The comparison of the LCOE with fossil fuel operated power plants showed that the considered renewable options can obtain significant lower LCOE. Highlights: CAPEX for photovoltaic drop up to 75%. CAPEX for wind turbines decreases up to 40% (onshore) and 50% (offshore). Photovoltaic LCOE will be the lowest in the future. LCOE shows highest sensitivity to annual full load hours and system CAPEX. Future LCOE based on fossil fuels will be higher than based on solar or wind.